IMPLEMENTASI PROGRAM NEW MANUFACTURING INDUSTRY DEVELOPMENT CENTER INDONESIA-JEPANG DALAM BIDANG SUMBER DAYA MANUSIA TAHUN 2019-2023 - Dewi, Sari Amalia; Kezia, Yohana Tasha Talitha (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This study analyzes the implementation of the New Manufacturing Industry Development Center (New MIDEC) within the bilateral cooperation framework between Indonesia and Japan under the Indonesia–Japan Economic Partnership Agreement (IJEPA) from 2019 to 2023. The research primarily focuses on human resource development in the industrial sector as part of a broader capacity-building strategy. A qualitative descriptive method was employed, utilizing document analysis and secondary data to assess the program’s implementation effectiveness. Theoretical frameworks include National Interest Theory to explain the strategic motivations of both countries, Economic Interest Theory to explore industrial impact, and Effectiveness Theory to evaluate program execution. Findings reveal that the New MIDEC program has not been fully effective in enhancing Indonesia’s industrial competitiveness and productivity. Key shortcomings include weak evaluation mechanisms, limited technology transfer, and inadequate monitoring by stakeholders. The program has largely emphasized basic training without yielding substantial improvements in national manufacturing performance. Strengthening institutional oversight, establishing clear performance indicators, and aligning stakeholder interests are essential to ensure the program contributes meaningfully to Indonesia’s industrial capacity development.